The Tartessian building of Casas del Turuñuelo (Guareña, Badajoz, Spain). : 2015-2022 Campaigns. - Celestino Pérez, Sebastián; Rodríguez González, Esther; Carranza Peco, Luis Miguel; Pulido González , Guiomar (Madrider Mitteilungen, 2024)
This paper brings together the results achieved during the excavation campaigns carried out at the tartessian building of Casas del Turuñuelo (Guareña, Badajoz, Spain) between 2015 and 2022. Along with the presentation of the documented spaces, some results corresponding to the study and analysis of objects documented during the excavation are presented execution of said works. Likewise, the article delves into two main aspects of the study of the site: the analysis of its architecture and the study of the imported materials documented throughout the archaeological work carried out. All this documentation updates the readings and interpretations that, to date, had been made of the Casas del Turuñuelo building and the final stage of Tartessus, developed in the Central Guadiana Valley.